2015
DOI: 10.11604/pamj.2015.20.288.5506
|View full text |Cite
|
Sign up to set email alerts
|

Fournier gangrene: rare complication of rectal cancer

Abstract: Fournier's Gangrene is a rare complication of rectal cancer. Its discovery is often delayed. It's incidence is about 0.3/100 000 populations in Western countries. We report a patient with peritoneal perforation of rectal cancer revealed by scrotal and perineal necrotizing fasciitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Local procedures and chronic indwelling catheters increase the risk of infection. Chemotherapy as a treatment for a previously diagnosed unrelated cancer was seen in 15% (3/20) of the case reports [3][4][5][6][7].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Local procedures and chronic indwelling catheters increase the risk of infection. Chemotherapy as a treatment for a previously diagnosed unrelated cancer was seen in 15% (3/20) of the case reports [3][4][5][6][7].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…CT has been proven to have greater specificity than plain film radiography or ultrasonography for identifying the process and the extent of the disease and can help to identify a local or distant malignancy [13]. Common CT findings of FG include soft-tissue stranding and edema, asymmetric fascial thickening, coexisting fluid collections, subcutaneous or deep soft tissue emphysema, or findings consistent with a mass lesion, invading the surrounding tissues [5,6]. In our review, CT was performed in 70% (14/20) of the patients; all patients showed at least one finding, and 85% (12/14) demonstrated a mass lesion with inflammation extending into soft tissue [7,12].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…5 Although few cases of FG developing through local spread of infection after rectum and sigmoid perforation have been reported in literature, to the best of our knowledge there has been only 1 case of FG developing from intestinal perforation with an inguinal hernia. [6][7][8][9] In this article we describe a case of colonic perforation peritonitis presenting with FG.…”
Section: Introductionmentioning
confidence: 97%